Semantic Adaptation of Arabic Loanwords in Javanese: A Study of the Translation of Alala - Alfina Nur Fadhilah; Mohammad Nu'man (Fakultas Tarbiyah dan Keguruan, 2026)
Purpose – This study investigates the integration of Arabic loanwords into Javanese as reflected in the translation of Alala, with the objective of identifying borrowed lexical items and analyzing their lexical and grammatical semantic changes. Design/methods/approach – Employing a qualitative descriptive design within a library research framework, the study systematically identifies Arabic-derived words in the translated text and compares their original meanings in Arabic with their contextual meanings in Javanese. Data were collected through close textual reading and classification, and analyzed using established theories of semantic change, including broadening, narrowing, shifting, and retention. Findings – The findings reveal 18 Arabic loanwords, of which 72.2% undergo semantic broadening, 16.7% experience semantic shifting, and 11.1% retain their original meanings, while no cases of narrowing are identified. These results indicate that lexical expansion constitutes the dominant mechanism of semantic integration in the analyzed corpus, particularly within pedagogical discourse shaped by pesantren translation traditions. Future research should incorporate broader corpora, comparative regional translations, and corpus-based quantitative methods to examine diachronic patterns and grammatical integration more comprehensively. Research Implications – The study contributes to contact linguistics, translation studies, and Islamic educational scholarship by demonstrating how pedagogical mediation influences long-term lexical development and semantic negotiation. However, the research is limited to a single translated text and a relatively small dataset, which constrains generalizability.